The Budget of a Local Government Unit on The Example of The City of Czestochowa During The SARS-Cov-2 Pandemic - Magdalena Roman (Communications of International Proceedings, 2021)
The following work presents the budget of a local government unit, its components, and also discusses the influence of the pandemic on the budgets of local government units. The influence of the pandemic on the components of the budget has been presented. The planning and implementation of the budget of the city of Czestochowa was taken into consideration as an example. The aim of the article is comparing the planned and implemented local government unit budget on the example of the city of Czestochowa in 2019-20. The expectations of local government members from the state in order to improve the poor financial condition of the local governments have been discussed in the conclusions.
Keywords: Budget; Local Government Unit; Finances